Copper-Catalyzed γ-Cyanation of Aza-Baylis–Hillman Adducts Using Trimethylsilyl Cyanide - Yadav, Arvind K.; Yadav, Lal Dhar S. (Synlett, 2015)
A copper-catalyzed γ-cyanation of aza-Baylis–Hillman adducts via iminium ion formation adjacent to benzylic tertiary amines has been developed using tert-butyl hydroperoxide (TBHP) as the external oxidant. The protocol involves in situ formation of 4π-conjugated iminium ion intermediates that undergo nucleophilic attack by cyanide to provide valuable γ-cyanated α,β-unsaturated amines.
Keywords: benzylic amines; Baylis–Hillman adducts; copper catalysis; cyanides; electron transfer; Michael addition